Festivalization of Music Patrol Bandulanand the Quest of Arek Bandulan Cultural Identity - Maftuchin, Annise Sri (UI Scholars Hub, 2016)
Futurologist Naisbitt (1988) Said about paradox of globalization process for local tradition culture, where tradition is exposed by the strength of global capitalism and modern life style. It does not always make the tradition to be crushed, but it becomes one kind, and even disappear. However, the tradition will try to find their place and the identity back. In this article, the discussion will be focused on how Arek Bandulan answer the global challenges through festivalization (Bennett, et al., 2014 ) the art of the musical tradition of their patrol. Festivalising art patrol is hold by Karangtaruna Wira Bhakti Bandulan who has spawned a lot of innovations in the appearance of various components local art in a festival. It shows that Arek Bandulan create their original cultural identity of art music tradition which is not too modern enough and not longer traditional too. The disclosure of identity expression to the global by festivalising traditions patrol sahur weaking up music art when Ramadan is packaged as well as events in the world and is supported by funder, the media and modern technologies. This ethnographic study tries to reveal how the process of identity formation in the object of patrol sahur festival happened.